2021
DOI: 10.21037/qims-20-1269
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric dual-energy CT to differentiate stage T1 nasopharyngeal carcinoma from benign hyperplasia

Abstract: Background: Stage T1 nasopharyngeal carcinoma (NPC T1 ) and benign hyperplasia (BH) are 2 common causes of nasopharyngeal mucosa/submucosa thickening without specific clinical symptoms. The treatment management of these 2 entities is significantly different. Reliable differentiation between the 2 entities is critical for the treatment decision and prognosis of patients. Therefore, our study aims to explore the optimal energy level of noise-optimized virtual monoenergetic images [VMI (+)] derived from dual-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(43 reference statements)
0
2
1
Order By: Relevance
“…Its relevance to the difference between NPC and BH is not as clear as that of shape features, but the negative coefficient consistently fitted by all folds might imply that BH has a higher LRHLE than NPC and therefore more homogeneous patches. Although early CNN studies have suggested that the performances of CNNs in discriminating between early NPC and BH in CT [32] and MRI [8,9] were higher than those reported for radiomics in this study, this ability of radiomics-that is, to identify specific features-provides a major advantage over CNNs in terms of understanding the results of machine learning studies.…”
Section: Discussioncontrasting
confidence: 69%
“…Its relevance to the difference between NPC and BH is not as clear as that of shape features, but the negative coefficient consistently fitted by all folds might imply that BH has a higher LRHLE than NPC and therefore more homogeneous patches. Although early CNN studies have suggested that the performances of CNNs in discriminating between early NPC and BH in CT [32] and MRI [8,9] were higher than those reported for radiomics in this study, this ability of radiomics-that is, to identify specific features-provides a major advantage over CNNs in terms of understanding the results of machine learning studies.…”
Section: Discussioncontrasting
confidence: 69%
“…Our findings are in accordance with the studies by Mileto et al and Chijie Xu et al and emphasize the value of DECT in abdominal oncologic imaging. Further studies have shown similar results for DECT Rho/Z measurements for other body regions, such as head and neck imaging, when differentiating benign from malignant thyroid nodules and T1 stage nasopharyngeal carcinoma from benign hyperplasia [33,34].…”
Section: Discussionmentioning
confidence: 56%
“…Additionally, dual-energy CT is a promising tool for the evaluation of non-traumatic acute abdomen, with its ability to characterize materials ( 17 ). Two types of reconstruction images acquired by DECT have been widely used: virtual monoenergetic images are helpful to differential diagnosis of tumors ( 18 , 19 ), and material decomposition images can quantity bone mineral density, liver iron content, and liver fat content ( 20 , 21 ). Dual-energy CT may help to characterize and distinguish different types of subphrenic foreign bodies, such as illegal intra-corporeal packets of cocaine and non-ferromagnetic projectiles ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%